Analytical performances of PENIA and PETIA urinary cystatin C determination allow tubular injury investigation. (March 2019) - Bargnoux, Anne-Sophie; Azoury, Vincent; Badiou, Stéphanie; Klouche, Kada; Plawecki, Maëlle; Kuster, Nils; ,; Cristol, Jean-Paul
Background: The study was designed to evaluate the analytical performances of two ERM-DA471/IFCC traceable cystatin C (CysC) reagents available on the market for urinary CysC (u-CysC) quantification. In addition, clinical relevance was assessed by measuring u-CysC in healthy controls and in patients with tubular dysfunction. Methods: CysC in urine was measured by a particle-enhanced nephelometric immunoassay using Siemens reagents and by a particle-enhanced turbidimetric immunoassay using DiaSys reagents. Imprecision, linearity, limit of detection and limit of quantification were evaluated according to CLSI recommendations. The two methods were tested on 150 urinary samples from 50 healthy subjects, 50 HIV patients with tubular dysfunction and 50 patients who developed acute kidney acute injury. Results: Within-laboratory coefficients of variations were below 4%. The lower limit of quantification of the assay was found at 0.043 and 0.046 mg/L for DiaSys and Siemens, respectively. The following Passing-Bablok regression equations were obtained: DiaSys = 0.99 Siemens + 0.00. Using Bland-Altman analysis, the mean bias was –0.004 mg/L on the analytical range between 0.02 and 1 mg/L. Median u-CysC in 50 HIV patients with tubular dysfunction and in 50 patients with AKI was higher than in control subjects. Conclusions: Both Siemens and DiaSys reagents demonstrated reliable and reproducible performances allowing easy determination of u-CysC on automated platforms in clinical practice with potential interest for the detection of tubular dysfunction.